Herpes Zoster in Solid Organ Transplantation: Incidence and Risk Factors - Kho, Marcia M. L.; Roest, Stefan; Bovée, Dominique M.; Metselaar, Herold J.; Hoek, Rogier A. S.; van der Eijk, Annemiek A.; Manintveld, Olivier C.; Roodnat, Joke I.; van Besouw, Nicole M. (Frontiers in Immunology, 2021)
Background Studies on herpes zoster (HZ) incidence in solid organ transplant (SOT) recipients report widely varying numbers. We investigated HZ incidence, severity, and risk factors in recipients of four different SOTs, with a follow-up time of 6–14 years. Methods Records of 1,033 transplant recipients after first heart (HTx: n = 211), lung (LuTx: n = 121), liver (LiTx: n = 258) and kidney (KTx: n = 443) transplantation between 2000 and 2014 were analyzed for VZV-PCR, clinical signs of HZ, and complications. Results HZ was diagnosed in 108 of 1,033 patients (10.5%): 36 HTx, 17 LuTx, 15 LiTx, and 40 KTx recipients. Overall HZ incidence rate after HTx (30.7 cases/1,000 person–years (PY)), LuTx (38.8 cases/1,000 PY), LiTx (22.7 cases/1,000 PY) and KTx (14.5 cases/1,000 PY) was significantly higher than in the general 50–70 year population. Multivariable analysis demonstrated age ≥50 years at transplantation (p = 0.038, RR 1.536), type of organ transplant (overall p = 0.002; LuTx p = 0.393; RR 1.314; LiTx p = 0.011, RR 0.444; KTx p = 0.034, RR 0.575), CMV prophylaxis (p = 0.043, RR 0.631) and type of anti-rejection therapy (overall p = 0.020; methylprednisolone p = 0.008, RR 0.475; r-ATG p = 0.64, RR1.194) as significant risk factors. Complications occurred in 33 of 108 (31%) patients (39% of HTx, 47% of LuTx, 20% of LiTx, 20% of KTx): post-herpetic neuralgia, disseminated disease, and cranial nerve involvement. Conclusion HZ incidence and severity in SOT recipients are most pronounced after heart and lung transplantation, in older patients, and when CMV prophylaxis is lacking.